Parâmetros bioquímicos de avaliação da função renal e hepática de equinos com cólica submetidos a laparotomia, sobreviventes ou não - Di Filippo, Paula Alessandra; Nogueira, Andressa Francisca Da Silva [UNESP]; Alves, Aracélle Elisane [UNESP]; Santana, Aureo Evangelista [UNESP] (FapUNIFESP (SciELO), 2012)
We examined 46 adult horses - six healthy, as control, (group 1) and 40 horses with colic submitted to treatment by laparotomy. Twenty animals had no postoperative complication (group 2), and twenty died or were euthanized from seven to ten days after the surgery (group 3). There was an increase in serum urea and creatinine concentration and AST, FA and GGT activity of animals from group 1 and group 2, indicative of renal and hepatic injury. The changes were associated with dehydration and endotoxins. Depending on the severity of the colic, animals may develop kidney and liver failure.
Biochemical parameters of evaluation of renal and hepatic function of colic horses submitted to laparotomy that have survived or not
Keywords: Acute abdomen; Clinical pathology; Horse; Animalia; Equidae